Simposio sobre Uncut: Introducción - Rosenblatt, Lucas (Análisis Filosófico, 2021)
On July 31, 2017, a symposium on Ripley’s forthcoming book Uncut was held in Buenos Aires. Ripley presented the main ideas in the book and there were comments by some of the participants. After the symposium, many of us agreed that it would be a good idea to put together a volume to reflect some of the interesting discussions that took place there.